Periglacial deposits as indicators of paleotemperatures. A case study in the Iberian Peninsula: The mountains of Galicia. (6th September 2019) - Viana‐Soto, Alba; Pérez‐Alberti, Augusto
Abstract: In this study, we provide a paleotemperature reconstruction based on periglacial deposits and landforms from the northwest Iberian Peninsula. We describe different types of periglacial deposits and landforms which were considered as paleoenvironmental archives. The occurrence of these landforms and deposits suggests that mean annual air temperatures must have been of ≤ −2°C for formation of block fields, block slopes and rock glaciers and ≥ 2°C for formation of stratified slope deposits, as indicated by their modern‐day analogs. The information obtained was used to construct paleotemperature maps by estimating temperature in relation to a standard altitudinal gradient. Two phases were differentiated. During the first phase, associated with the Maximum Glacial Advance (MGA) before 30 ka cal BP, the prevailing snow conditions favored the formation of stratified slope deposits and genesis of glaciers in all of the mountain systems, without the presence of permafrost. During the second phase, associated with the Glacial Maximum (GM) between 21 and 25 ka cal BP, colder conditions favored the presence of permafrost and genesis of block fields, block slopes and rock glaciers at elevations above 700 m. Temperature estimations ranged between around +6°C and − 6°C at an elevation of 2, 000 m for the first phase, and between +2°C and − 10°C for the second phase. Due to limitations in estimating past climate conditions, the results should be considered as a first approximation to define northwest Iberian Peninsula paleotemperatures for the Late Pleistocene.